Effect of Different Fat and Moringa oleifera Leaf Meal (MOLM) Inclusion Levels on Proximate Composition, Fatty Acid Profile, and Lipid Oxidation of Chicken Droëwors. (6th September 2022) - Tembela, Nelisiwe; Mukumbo, Felicitas Esnart; Hugo, Arno; Jaja, Ishmael Festus
Abstract : We present the first report on the effect of graded levels of Moringa oleifera leaf meal (MOLM) (0, 0.25, and 0.5%) and fat (0, 10, and 15%) on fatty acid profile, lipid oxidation, and proximate composition of chicken droëwors. On triplicate samples of all treatments, proximate analysis was done, the total lipid was quantitatively extracted using chloroform and methanol in a ratio of 2 : 1, fatty acid profiles were determined, and thiobarbituric acid reactive substances (TBARS) were measured. The present study showed that droëwors manufactured with 0% fat inclusion had less fat and more protein than those made with 10% and 15% fat. All treatments contained a greater percentage of C18:1c9 (oleic) (30.95 to 32.65%) acid than other fatty acids and a higher proportion of unsaturated fatty acids than saturated. T9 (15% fat, 0.5% MOLM) had significantly (P < 0.05 ) higher PUFAs than T1 (0% fat, 0% MOLM) and T4 (10% fat, 0% MOLM). Treatments with 0.5% MOLM had significantly lower TBARS values after drying (0.01-0.07 mg MDA/kg) than treatments with 0% and 2.5% MOLM (0.05–0.15 mg MDA/kg). Therefore, MOLM inclusion at 0.25 and 0.5% effectively decreased TBARS of chicken droëwors with up to 15% fat inclusion after 72 h of drying and 168 h of storage and is a potentially good source of natural antioxidants for this traditional dried sausage product.